MOL-PCR and xMAP Technology: A Multiplex System for Fast Detection of Food- and Waterborne Viruses - Hrdy, Jakub; Vasickova, Petra; Nesvadbova, Michaela; Novotny, Jiri; Mati, Tomas; Kralik, Petr (The Journal of molecular diagnostics, 2021)
Viruses are common causes of food- and waterborne diseases worldwide. Conventional identification of these agents is based on cultivation, antigen detection, electron microscopy, or real-time PCR. Because recent technological advancements in detection methods are focused on fast and robust analysis, a rapid multiplexing technology, which can detect a broad spectrum of pathogenic viruses connected to food or water contamination, was utilized. A new semiquantitative magnetic bead-based multiplex system has been designed for simultaneous detection of several targets in one reaction. The system includes adenoviruses 40/41 (AdV), rotavirus A (RVA), norovirus (NoV), hepatitis E virus (HEV), hepatitis A virus (HAV), and a target for external control of the system. To evaluate the detection system, interlaboratory ring tests were performed in four independent laboratories. Analytical specificity of the tool was tested on a cohort of pathogenic agents and biological samples with quantitative PCR as a reference method. Limit of detection (analytical sensitivity) of 5 × 100 (AdV, HEV, and RVA) and 5 × 101 (HAV and NoV) genome equivalents per reaction was reached. This robust, senstivie, and rapid multiplexing technology may be used to routinely monitor and manage viruses in food and water to prevent food and waterborne diseases.
Keywords: polymerázová řetězová reakce; Food Microbiology; Polymerase Chain Reaction; viry; Limit of Detection; Water Microbiology; limita detekce; Humans; mikrobiologie vody; Viruses; potravinářská mikrobiologie; lidé